HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN KECEMASAN SOSIAL PADA REMAJA (Di Kelas IX SMPN 1 Berbek Kabupaten Nganjuk) - Heru Wahyudi; Rahayu Budi Utami; Abdullah Catur Nugroho (LPPM STIKes SATRIA BHAKTI NGANJUK, 2025)
Social anxiety in adolescents takes the form of a direct or indirect decreasein the quality of social interactions caused by excessive use of social media. The aim ofthis research is to determine the relationship between the intensity of social media use andsocial anxiety in adolescents (in class IX of SMPN 1 Berbek, Nganjuk Regency).